Virtuous Justice, and its Price in Truth in Post-Dictatorial Argentina - Hilb, Claudia Beatriz (2011)
"What happened? Why did it happen? How could it have happened?" These are, says Hannah Arendt, "the questions with which my generation had been forced to live for the better part of its adult life". These are also, the questions which my generation - the generation of the victims of the Argentine military dictatorship and of the radical leftist militants of the 1970s - has been forced to live with for the better part of its adult life. These questions, along with the difficult task of formulating answers to them, are what I would like to briefly address here.